The facts of life - Harold J. Morowitz (Oxford University Press, 1992)
The question of whether abortion should or should not be permitted, and under what circumstances, is among the most difficult and sometimes anguished decisions for contemporary men and women. How we feel about this issue, and what actions we take, help to define our image of who we are as social beings. In the midst of the surrounding political, ethical, and religious debate, people everywhere are once again examining their conscience and their beliefs, and turning to unutilized sources of information as they seek to come to terms with this contentious issue. And as emotions run high, it is helpful to step back from the highly charged arena to reconsider the underlying scientific facts about human development...